Prevalence of neurodegenerative diseases in elderly people at a reference center in Belém - PA (Research, Society and Development, 2022)
The study aims to identify the prevalence of these diseases in elderly people cared for at a health unit in Belém - Pará. The cross-sectional, observational and descriptive statistical study with 470 elderly medical records observed a prevalence of 7.9% of Depression, not consistent with others studies that estimate higher prevalence, no association with older age with similar distribution between genders was observed. Regarding dementia and Parkinson's disease, there was also no change related to gender, the distribution between age groups was greater in those over 70 years old. It is concluded that the main factor associated with the three clinical conditions was aging, being essential to allow it to be healthy and successful, with control of risk facts for neurodegenerative diseases and good social and family support.